2021
DOI: 10.3390/ijerph18168718
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Importance of Social Aspects in Ikigai among Older Women

Abstract: Ikigai is a unique Japanese concept that encompasses not only joy and happiness, but also the purpose and meaning of life. The purpose of this study was to explore the factors that contribute to Ikigai, an important concept in the health of older women, and to clarify the relationship between Ikigai and the enhancement of the social aspects of their health. The participants in this longitudinal study, conducted between October 2017 and February 2020, were physically healthy older women aged 65 years and above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The relation of ikigai and DSA is also consistent with studies showing that maintenance of and increases in the number of weak and strong social connections is protective against potential declines in ikigai, along with studies causally linking the number of social activities to ikigai (but not physical functioning) [ 55 ]. Furthermore, there are several studies exploring the positive effects of leisure on ikigai.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The relation of ikigai and DSA is also consistent with studies showing that maintenance of and increases in the number of weak and strong social connections is protective against potential declines in ikigai, along with studies causally linking the number of social activities to ikigai (but not physical functioning) [ 55 ]. Furthermore, there are several studies exploring the positive effects of leisure on ikigai.…”
Section: Discussionsupporting
confidence: 82%
“…Survey participants’ ikigai-9 scores averaged 28.38 (SD 6.08; range 13-44). Although the ikigai-9 scale does not specify the determination of ikigai levels based on score, previous literature found the average ikigai-9 scores for a sample of Japanese older adults to be 29.7 (SD 6.3) [ 55 ], whereas another found it to be 33.9 for a “high life purpose” group of community-dwelling older adults in Japan [ 92 ]. Scores here, therefore, are likely consistent with those of “average” Japanese older adults and represent participants having a wide range of ikigai.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the ikigai-9 scale does not specify a determination of ikigai levels based on score, we do note that scores tended to be high, with 33 participants scoring between 35 and 45 (the maximum); all survey participants’ scores averaged 37.1 (SD = 5.7). For comparison, previous literature found the average ikigai -9 score to be 29.7 (SD = 6.3) for one sample of Japanese OAs ( Seko and Hirano, 2021 ), while another found it to be 33.9 for a “high life purpose” group of community-dwelling OAs in Japan ( Tsuzishita and Wakui, 2021 ).…”
Section: Resultsmentioning
confidence: 91%
“…The mechanisms accounting for these effects are not well understood, though evidence suggests that increased activity levels may offer a protective effect by mitigating depression and the onset of disability. Recent research indicates that the development of a sense of life purpose and meaning via activity may foster social activities and minimize mortality risk (Alimujiang et al, 2019; Seko & Hirano, 2021). As well, evidence from a lifestyle intervention with ethnically diverse older adults has shown that the significance, or meaningfulness, of therapeutic activity may account for lower levels of depression compared with no treatment controls (Juang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%